Pendampingan Pengembangan Perangkat Evaluasi Berbasis Hots Bagi Guru SD Muhammadiyah Jakarta Timur - Martriwati Martriwati; Burhayani Burhayani; Ana Natalia (Jurnal Abdimas Adpi Sosial dan Humaniora, 2023)
The Community Service (PKM) activity was done in collaboration with  Muhammdiyah Elementary School 3 Matraman, East Jakarta with the total participants involved 15 teachers. The problems faced by teachers in this school are their lack of conceptual understanding of assessments based on High Order Thinking Skill (HOTS) and the weak ability of teachers in making evaluation sets that meet the HOTS standards themselves. The HOTS evaluation criteria have been set in Curriculum 13 where this curriculum is a nationally applicable curriculum in Indonesia. The training approach uses an interactive-communicative approach which is reflected in all stages of training; the discussion, practice, and presentation stages. The implementation of community service activities was carried out in online for 3 days. The discussion material is related to the HOTS concept where teachers were trained and guided to make their respective questions according to the concepts that have got  a day before. This mentoring activity is focused on increasing the knowledge and ability of teachers to make evaluation sets containing HOTS content. Therefore, in this PKM activity, teachers were given theoretical and practical knowledge through training and guidance in the preparation of assessment according to their subject. The result of this training and mentoring is felt to be very useful for teachers and it is revealed from the results of the questionnaire where teachers have been able to analyze the samples of formative and final test whether they have fulfilled the criteria of HOTS or not.